The Concept of 'Ain (Evil Eye) in the Qur'an and Hadith: Implications for Mental Health in Contemporary Era - Nurfajriyani; Latukau, Ratu Essya Putri; Yasir, Muhammad; Al-Nussairi, Wissam Farhan (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the concept of 'Ain disease from the perspective of the Qur'an and Hadith, as well as its implications for mental health in the contemporary era. In the modern context, phenomena such as jealousy and envy, often triggered by exposure to social media, can affect an individual's mental well-being, leading to stress, anxiety, and depression. The data used in this research was obtained through literature studies on Qur'anic texts, Hadith, and contemporary psychological studies related to mental disorders influenced by social factors. This research employs a qualitative approach with a hermeneutic method to analyze the understanding of 'Ain disease and explore its connection to current psychological symptoms. The findings show that 'Ain disease, as a manifestation of the negative effects of jealousy, is closely related to the mental disorders commonly experienced by modern society. The social stigma surrounding 'Ain disease further exacerbates this condition, as many individuals are reluctant to seek psychological help. Therefore, a holistic approach that integrates spiritual and psychological understanding, as well as raising awareness about mental health, is essential to mitigate the negative effects of 'Ain disease. Contribution: This research contributes to the development of mental health studies within religious and contemporary contexts, highlighting the importance of integrating spiritual and psychological approaches in addressing mental health challenges in society.